EFFECTIVENESS OF OJK STIMULUS POLICY, ACCOUNTING OF QARDH FUNDS ON SOLVENCY LEVEL (DURING COVID 19 PANDEMIC) IN THE SHARIA LIFE INSURANCE SECTOR IN INDONESIA - Nano Suyatna (SEAN Institute, 2022)
This study aims to assess the effectiveness of OJK Stimulus and Qardh Fund Accounting in anticipating deficiencies in the Solvency Level of the Islamic life insurance sector as the impact of the Covid 19 Pandemic. The research method used is Statistical Analysis and Data Visualization of Risk Based Capital Islamic Life Insurance for the period 2020.Q1 – 2020. Q4. The purpose ia to analyze the effect of OJK stimulus, Qardh Accounting on the Solvency Level of sharia life insurance companies during the Covid 19 Pandemic. The results showed that there was a significant influence. This is proved by the existence of several sharia life insurance companies that have experienced a deficiency in the adequacy of the Minimum Solvency Level. With the existence of a Qardh Fund loan, the Solvency Deficiency Level can be overcome. The Fund Manager is required to cover this shortfall by using a Qardh Fund loan to maintain the going concern of a sharia life company.